2010
DOI: 10.1021/es903737k
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Speciation of Pb in Urban Road Dust Sediment: A XANES and EXAFS Study

Abstract: The quality of the urban environment is of growing concern as its human population continues to dramatically increase. X-ray absorption spectroscopy (XAS) and SEM have been used to study the solid-phase speciation of Pb in urban road dust sediments (RDS) in Manchester, UK. XANES analysis and linear combination modeling indicate that PbCrO(4) and Pb-sorbed goethite occur in 1000-500 microm, 250-125 microm, 63-38 microm, and <38 microm size fractions, collectively representing between 51-67% of the contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 46 publications
4
43
0
Order By: Relevance
“…Suzuki and Ono (2008) considered PbO 2 as a reducible fraction and PbS as an oxidizable fraction. The F(3)-Pb fraction may also include Pb(II) associated with iron(III) (hydroxide)oxide (Barrett et al, 2010). The results of the chemical resistance test for Pb were consistent with earlier reports.…”
Section: Rd-j(b) Rd-j(u) Rd-k(b) Rd-k(u) Rd-f(b) Rd-f(u)supporting
confidence: 90%
“…Suzuki and Ono (2008) considered PbO 2 as a reducible fraction and PbS as an oxidizable fraction. The F(3)-Pb fraction may also include Pb(II) associated with iron(III) (hydroxide)oxide (Barrett et al, 2010). The results of the chemical resistance test for Pb were consistent with earlier reports.…”
Section: Rd-j(b) Rd-j(u) Rd-k(b) Rd-k(u) Rd-f(b) Rd-f(u)supporting
confidence: 90%
“…Sequential chemical extraction of lead from urban dust samples showed that, beside the residual phases, oxidizable, reducible and easily extractable fractions may also contain high amounts of lead (Banerjee 2003). These findings correspond to the observations of Barrett et al (2010) who found that Pb occurs primarily in the form of Pb-sorbed goethite, as well as lead chloride, carbonate, oxide and phosphate in urban dust.…”
Section: Introductionsupporting
confidence: 86%
“…X-Ray spectroscopy analyses by Barrett et al (2010) showed several lead phases in urban dust, such as surface-sorbed lead, lead chloride, lead carbonate, lead oxide and lead phosphate, which are potentially soluble in weak mineral acids to varying degrees. These are mostly the same phases controlling aqueous-solid partitioning of lead in natural systems.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that roadside soils are still impacted by petrol-derived Pb even after the phasing out of leaded petrol (Bäckström et al, 2004). A number of Pb-bearing species in road dust have low solubility at typical soil pH and E h values, and therefore are likely to persist (Barrett et al, 2010). Along with direct aerosol deposition, other pathways in which road dust could be incorporated into the alluvial soils are either from direct road drainage or drainage derived from sewage works that feed into the Trent and has been dispersed by flooding.…”
Section: Source Apportionmentmentioning
confidence: 99%